The Minutemen and Anti-immigration Attitudes in California - Frédérick Douzet (European Journal of American Studies)
This paper examines the role of the Minutemen in building up popular pressure for immigration reform and capturing the growing frustration of some of residents at the way the Bush administration is handling immigration in a context of heightened fear about national security. The immigration issue in California had quieted down after anti-immigration proposition 187 was passed –yet never enacted- in 1994. Pete Wilson had unsuccessfully used this divisive issue to win presidential nomination, alienating minority voters in the State and therefore undermining the strength of the Republican party.Despite an apparent growing tolerance about diversity and good economic times, the issue came back to California both through the deterioration of the situation at the border and through the national debate over immigration reform in the mid-2000s. Based on field work at the California-Mexican border, the author gives a portrait of the Minutemen, explaining their motivations, hopes, fears and action which help understand the perceptions and strategies of congressmen and legislators and the fascinating radicalization of their positions on immigration over the past two years.